2010
DOI: 10.1021/jf9041613
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Intestinal Absorption of Carotenoids Delivered as Molecular Inclusion Complexes with β-Cyclodextrin Is Not Inhibited by High-Density Lipoproteins

Abstract: This study analyzed the assimilation efficiency of carotenoids when they are delivered as inclusion complexes with beta-cyclodextrin (CyDIC) in water. The in vitro assimilation model used was the brush border membrane vesicles (BBMV) system in which the BBMVs were incubated with CyDIC. Carotenoid suspensions in Tween were used as a reference. Regardless of the form in which the carotenoids were delivered to the BBMV preparation, a higher assimilation efficiency was observed for carotenes than for the xanthophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…After some incubation time, the solution is filtered or centrifuged to separate the BBMV fraction and the buffer. This technique has been used successfully in mechanistic studies of the assimilation of glucose, biliary salts, lipids, xenobiotics, cholesterol and carotenoids (Alcorn, Simpson, Leahy, & Peters, 1991;Burckhardt, Kramer, Kurz, & Wilson, 1983;Fernández-García, Carvajal-Lérida, Rincón, Ríos, & Pérez-Gálvez, 2010;Hopfer, Nelson, Perrotto, & Isselbacher, 1973;Ikeda, Tanaka, Sugano, Vahouny, & Gallo, 1988;Keelan, Burdick, Wirzba, & Thomson, 1992;Kessler et al, 1978;Ling, Lee, & Hollander, 1989;Moore, Gugger, & Erdman, 1996;Proulx, McNeil, Biglez, & Williamson, 1982). Intestinal tissue from pigs, rabbits, chickens, rats, mice, and humans has been used in these studies, although human BBMV studies are less frequent due to the limited availability of tissue in the conditions necessary for these trials.…”
Section: In Vitro Absorption Modelsmentioning
confidence: 99%
“…After some incubation time, the solution is filtered or centrifuged to separate the BBMV fraction and the buffer. This technique has been used successfully in mechanistic studies of the assimilation of glucose, biliary salts, lipids, xenobiotics, cholesterol and carotenoids (Alcorn, Simpson, Leahy, & Peters, 1991;Burckhardt, Kramer, Kurz, & Wilson, 1983;Fernández-García, Carvajal-Lérida, Rincón, Ríos, & Pérez-Gálvez, 2010;Hopfer, Nelson, Perrotto, & Isselbacher, 1973;Ikeda, Tanaka, Sugano, Vahouny, & Gallo, 1988;Keelan, Burdick, Wirzba, & Thomson, 1992;Kessler et al, 1978;Ling, Lee, & Hollander, 1989;Moore, Gugger, & Erdman, 1996;Proulx, McNeil, Biglez, & Williamson, 1982). Intestinal tissue from pigs, rabbits, chickens, rats, mice, and humans has been used in these studies, although human BBMV studies are less frequent due to the limited availability of tissue in the conditions necessary for these trials.…”
Section: In Vitro Absorption Modelsmentioning
confidence: 99%
“…Notwithstanding morphological agglomeration, the capacity of WDBC-IC to dissolve in water and release the guest molecules may be regarded as an improvement to carotenoid inclusion complexes in general and a comparable alternative to Eudragit ™ -encapsulated vitamin A in terms of burst release in simulated gastric digestion (Anselmo et al, 2019). High concentrations of BC in the digesta also support the conclusion that a surfactant in the inclusion complex may enhance assimilation (Fernández-Garcıá et al, 2010). However, other strategies can be investigated to stabilise β-carotene levels throughout gastrointestinal degradation.…”
Section: In Vitro Digestionmentioning
confidence: 71%
“…Later, an electrospraying technique was applied to BC emulsions, but the resulting microencapsulation efficiency was only 34%, slightly lower than conventional spray drying (Donhowe et al, 2014;Gómez-Mascaraque et al, 2017). Suitable surfactants have also been used in preparing BC-based inclusion complexes with amylose to alter the tendency of BC to hinder crystal formation (Kong et al, 2018) and also to facilitate assimilation of BC from β-cyclodextrin complexes to intestinal brush border membranes (Fernández-Garcıá et al, 2010). Liposomes containing vitamin C and BC have been reported to be 98% efficient in encapsulation and cumulatively release 50-80% of the payload after simulated intestinal digestion (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…3), which has also been explored in lutein bioavailability studies [63,67]. Cyclodextrines are cyclic oligomaltosaccharides obtained from starch by means of an enzymatic cycling reaction using cyclodextrin glucosyltransferase [67]. These preparations are made through the addition and mixing of lipophilic guest molecules into a cyclodextrin aqueous solution.…”
Section: Xanthophyll Formulations Not Yet Studied For Xanthophyll Stamentioning
confidence: 99%
“…b-Cyclodextrins (b-CD) are a family of cyclic oligosaccharides composed of a-(1-4) linked 6-,7-or 8-D-glucose units known to accommodate hydrophobic molecules and to form water-soluble inclusion complexes [63]. It has been shown that assimilation of xanthophyll-b-CD aqueous solutions is higher than the obained when the compounds are suspended in Tween [67] or liposome carriers [63]. However, an important disadvantage of this technology is the high volumes needed to develop xanthophyll-based products for parenteral administration, since 5 L of solution are required to deliver 10 mg of astaxanthin [69].…”
Section: Xanthophyll Formulations Not Yet Studied For Xanthophyll Stamentioning
confidence: 99%